Pengembangan Metode Alternatif Penyelesaian Sengketa Bisnis Berdasarkan Kearifan Lokal Melalui Jalur Mediasi - Deiredja, Yurika Dibba Destari; Pangestu, Rizky Gelar; Haykal, Hassanain Haykal (Zenit, 2013)
Conflict that occur in the society, generally can be settled by two ways, litigation and non litigation. Non litigation dispute settlement has several alternatives. In theoritical and practical  field, non litigation dispute settlement need to be developed dynamicly adapted with social changes. Development of alternative method can be adopted from the value of indigenous knowledge, so the result can comply with sense of justice. The indigenous Knowledge in question are there values that are implemented in local society themselves. In addition to the written rules that apply in the local society for the dispute resolution process. The implementation of Alternative Dispute  Resolution based on indigenous knowledge can be seen from the settlement of disputes in the local society in Indonesia.  Keyword : Method, Alternative Dispute Resolution, Indigenous Knowledge